Laboratory flume experiments with the Swiss plate geophone bed load monitoring system: 1. Impulse counts and particle size identification. Issue 10 (9th October 2016) - Wyss, Carlos R.; Rickenmann, Dieter; Fritschi, Bruno; Turowski, Jens M.; Weitbrecht, Volker; Boes, Robert M.
Abstract: We performed systematic flume experiments using natural bed load particles to quantify the effect of different parameters on the signal registered by the Swiss plate geophone, a bed load surrogate monitoring system. It was observed that the number of impulses computed from the raw signal clearly depends on bed particle size, mean flow velocity, bed roughness, and to a minor extent on particle shape. The centroid frequency of the signal resulting from the collision of a bed load particle against the geophone plate was found to be inversely related to particle size but to be less sensitive to variations in mean flow velocity and bed roughness than the signal amplitude, which is also related to particle size. Combining frequency and amplitude information resulted in a more robust identification of the transported particles size over a wide range of sizes than using amplitude information alone. Key Points: Systematic flume experiments with the Swiss plate geophone system were performed Amplitude and frequency information are combined to identify particle size Characteristic signal values of the Swiss plate geophone system are established with flume experiments